Performance evaluation of Baermann techniques: The quest for developing a microscopy reference standard for the diagnosis of Strongyloides stercoralis. - Woyneshet Gelaye; Nana Aba Williams; Stella Kepha; Augusto Messa Junior; Pedro Emanuel Fleitas; Helena Marti-Soler; Destaw Damtie; Sissay Menkir; Alejandro J Krolewiecki; Lisette van Lieshout; Wendemagegn Enbiale; Stopping Transmission of Intestinal Parasites (STOP) (Public Library of Science (PLoS), 2021)
Background Soil-transmitted helminths (STH) are common in low and middle income countries where there is lack of access to clean water and sanitation. Effective diagnosis and treatment are essential for the control of STH infections. However, among STH parasites, Strongyloides stercoralis is the most neglected species, both in diagnostics and control strategies. Diagnostic methods cover different approaches, each with different sensitivities and specificities, such as serology, molecular techniques and microscopy based techniques. Of the later, the Baermann technique is the most commonly used procedure. In the literature, several ways have been described to perform the Baermann method, which illustrates the overall lack of a '(gold) reference standard' method for the diagnosis of S. stercoralis infection. In this study we have evaluated the performance of three Baermann techniques in order to improve the reference standard for the microscopic diagnosis of S. stercoralis infection thereby facilitating individual case detection, mapping of the disease and proper evaluation of treatment responses. Methods/principal findings A community based cross sectional study was conducted at Zenzelima, Bahir Dar Zuria Ethiopia. A total of 437 stool samples were collected and analyzed by the following procedures: conventional Baermann (CB), modified Baermann (MB), and modified Baermann with charcoal pre-incubation (MBCI). The diagnostic sensitivity and Negative Predictive Value (NPV) of each technique was calculated using the combination of all the three techniques as a composite reference standard. Our result indicated that larvae of S. stercoralis were detected in 151 (34.6%) stool samples. The prevalence of S. stercoralis infection based on the three diagnostic methods was 9.6%, 8.0%, and 31.3% by CB, MB, and MBCI respectively. The sensitivity and NPV for CB, MB, and MBCI were 26.7% and 70.8%, 22.1% and 69.6%, and 87.0% and 93.2%, respectively. The MBCI showed significant difference (P- value = <0.001) in the sensitivity and NPV values when compared with CB and MB values. The agreement between CB, MB, and MBCI with the composite reference standard was 31.8%, 26.7%, 89.6%, respectively. Conclusion/significance Our results suggest the superior performance of MBCI. It is relatively easy to implement, simple to perform and comparatively cheaper. The CB is by far the commonly used method in routine diagnostic although this technique significantly underestimates the true burden of the disease and thereby contributing to the exclusion of S. stercoralis from the control strategies. Therefore, MBCI is recommended as a routine microscopy-based diagnostic test for S. stercoralis infection, particularly in settings where molecular procedures are not available.